Bioactive properties and antioxidant capacity of oils extracted from citrus fruit seeds - Silva, A. C. [UNESP]; Jorge, N. [UNESP] (Akademiai Kiado Zrt., 2019)
This study aimed at identifying the presence of bioactive compounds and evaluating the antioxidant capacity of oils extracted from citron, kinkan, and orange. Therefore, determination of fatty acid profi le, tocopherol and phytosterol composition, phenolic compounds, and total carotenoids was performed in the oils extracted from seeds. To determine the antioxidant capacity, the tests DPPH, ABTS+, FRAP, carotene/linoleic acid, and oxidative stability were performed. The citrus fruit seeds presented high lipid level, with predominance of unsaturated fatty acids, especially linolenic essential fatty acid, with 7.9 and 8.5% in citron and kinkan seed oils, respectively. The presence of tocopherols and phytosterols induced a higher antioxidant capacity on the oils analysed. The collected information might help new alternative sources of vegetable oils obtained from agroindustrial waste to serve as raw material for food, chemical, and pharmaceutical industries.
Keywords: Antioxidants; Bioactive compounds; Citrus fruit; Extraction; Oxidative stability; Vegetable oils